2007
DOI: 10.1200/jco.2006.09.3484
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study on the Effect of Disease Sites, Age, and Prior Therapy on Response to Iodine-131-Metaiodobenzylguanidine Therapy in Refractory Neuroblastoma

Abstract: The high response rate and low nonhematologic toxicity with 131I-MIBG suggest incorporation of this agent into initial multimodal therapy of neuroblastoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
193
4
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(206 citation statements)
references
References 23 publications
5
193
4
4
Order By: Relevance
“…In a large phase II study, 164 patients with relapsed or refractory neuroblastoma were treated with 131 I-MIBG. Approximately one-third of patients (36%) had evidence of clinical response; with approximately one-third (34%) having stable disease for a median of 6 months [117], leading to efforts to include 131 I-MIBG therapy as a part of upfront consolidation treatment for children with high-risk neuroblastoma. Additional clinical trials are ongoing through the New Agents in Neuroblastoma Therapy (NANT) consortium to identify the best of anticancer agents to combine with MIBG therapy (NCT02035137).…”
Section: Treatment -Relapsed and Refractory Neuroblastomamentioning
confidence: 99%
“…In a large phase II study, 164 patients with relapsed or refractory neuroblastoma were treated with 131 I-MIBG. Approximately one-third of patients (36%) had evidence of clinical response; with approximately one-third (34%) having stable disease for a median of 6 months [117], leading to efforts to include 131 I-MIBG therapy as a part of upfront consolidation treatment for children with high-risk neuroblastoma. Additional clinical trials are ongoing through the New Agents in Neuroblastoma Therapy (NANT) consortium to identify the best of anticancer agents to combine with MIBG therapy (NCT02035137).…”
Section: Treatment -Relapsed and Refractory Neuroblastomamentioning
confidence: 99%
“…It is thought that emission of ionising radiation at this site results in tumour decay (Mukherjee et al, 2001;Rose et al, 2003;Pasieka et al, 2004). This therapy has been used to treat NETs of various types, including gastroenteropancreatic NETs (Pathirana et al, 2001;Pasieka et al, 2004;Safford et al, 2004;Sywak et al, 2004;Buscombe et al, 2005), paraglangliomas (Mukherjee et al, 2001;Safford et al, 2003;Fitzgerald et al, 2006), phaeochromocytomas (Castellani et al, 2000;Rose et al, 2003;Safford et al, 2004;Fitzgerald et al, 2006), medullary carcinoma of the thyroid (Castellani et al, 2000(Castellani et al, , 2003Mukherjee et al, 2001) and neuroblastomas (Howard et al, 2005;Matthay et al, 2007). A number of previous studies had demonstrated significant symptomatic benefit in 40 -60% of patients with metastatic NETs following 131 I-MIBG therapy (Safford et al, 2004;Sywak et al, 2004), in a safe and cost-effective manner (Pathirana et al, 2001).…”
mentioning
confidence: 99%
“…With the widespread use of therapeutic 131 I-mIBG as a targeted radiopharmaceutical treatment of neuroblastoma both in newly diagnosed and relapsed patients, diagnostic mIBG scans will determine the eligibility for this modality (Garaventa et al, 1999;Gaze et al, 2005;Matthay et al, 2006Matthay et al, , 2007de Kraker et al, 2008;DuBois and Matthay, 2008). Previous studies have indicated that a positive mIBG scan after induction chemotherapy or just before myeloablative therapy may be a prognostic marker for a high likelihood of relapse (Ladenstein et al, 1998;Perel et al, 1999;Schmidt et al, 2008).…”
mentioning
confidence: 99%